Erzhi Pill® Protected Experimental Liver Injury Against Apoptosis via the PI3K/Akt/Raptor/Rictor Pathway - Hai-Mei Zhao; Xiao-Yun Zhang; Xiu-Yun Lu; Song-Ren Yu; Xin Wang; Yong Zou; Zheng-Yun Zuo; Duan-Yong Liu; Bu-Gao Zhou (Frontiers Media S.A., 2018)
Erzhi Pill (EZP) is one of the basic prescriptions for treating liver diseases in traditional Chinese medicine. However, its mechanism of action is still undefined. The PI3K/AKT/Raptor/Rictor signaling pathway is closely related to apoptosis and plays a significant role in the pathogenesis of liver disease. To define the mechanism of the hepatoprotective effect of EZP in the treatment of liver disease, hepatic injury induced by 2-acetylaminofluorene/partial hepatectomy was treated by EZP for 14 days. The therapeutic effect of EZP was confirmed by the decreased production of aspartate aminotransferase and alanine aminotransferase, recovery of pathological liver injury, followed by inhibition of pro-inflammatory cytokines and transforming growth factor-β1. Bromodeoxyuridine assay and TUNEL staining indicated that apoptosis was suppressed and the numbers of cells in S phase and G0/G1phase were decreased. The crucial proteins in the PI3K/AKT/Raptor/Rictor signaling pathway were deactivated in rats with experimental liver injury treated by EZP. These results indicated that the hepatoprotective effect of EZP via inhibition of hepatocyte apoptosis was closely related to repression of the PI3K/Akt/Raptor/Rictor signaling pathway.